Prinsip – Prinsip Ekonomi Islam dalam Perspetif IPTEKS - Azkiya Fantasyiru Fadhila; Endang Wahyuningsih; Nelsya Cili Aira Rinaldi; Erni Sulistiyowati; Susi Tri Susanti; Syamilah Syamilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to explore the principles of Islamic economics in adapting to the rapid developments in science, technology, and arts (STEM). Islamic economics focuses on several aspects, including material, spiritual, and moral dimensions. This illustrates that the principles of Islamic economics should be applied to a broader environment, including developments in science, technology, and arts (STEM). Islamic economics is a system that adheres to the principles of Islamic law (Sharia). The concept of Islamic economics includes: Balance, Justice, and Safety, which serve as the foundation for resource management. There are many opportunities within Islamic economics to establish a new financial system, such as reporting and recording based on Sharia and utilizing more optimal technology. The application of this new Sharia financial system plays an important role in strengthening the principles of Islamic economics, including the prohibition of usury (riba), uncertainty (gharar), unjust distribution of wealth, and investments that harm the community. Investment in Islamic economics is a means of placing funds with the aim of generating profit, while adhering to the principles of Islamic economics, making it a permissible activity that avoids elements of usury, gambling (maysir), and uncertainty (gharar). The implementation of these principles of Islamic economics will ultimately benefit the community and prevent any harm. People must pay more attention to the legal foundations set by Sharia, which provides clear guidelines for a prosperous and balanced life, covering both social and economic aspects as well as the environment.